Risk factors associated with self-medication among women in Iran - Mahmood Karimy; Majed Rezaee-Momtaz; Mahmoud Tavousi; Ali Montazeri; Marzieh Araban (BMC, 2019)
Abstract Background Self-medication is a public health concern that may create several problems such as increase in drug resistance, raise in drug use per capita, and creating side effects. This study was conducted to determine predictors of self-medication based on the theory of planned behavior (TPB) among the Iranian women. Methods This was a cross sectional study. A sample of married women completed a validated, anonymous, self-administered questionnaire. The questionnaire included items on demographic variables, knowledge, and TPB structures, and the checklist of women's self-medication practices. The study was conducted in six urban health centers of Shush and Zarandieh in Iran during January to July 2016. Data were analyzed using SPSS 23.0 applying t-test and logistic regression. Results A total of 360 women took part in the study. The results showed that 76% of women had a history of self-medication and 98.9% stored drugs at home. The most important reasons for self-medication were perceived self-medication harmless (41%), having history of a disease (35.5%), and availability of medications at home (34%). The most frequent diseases for self-medication were fatigue, weakness, and anxiety (24%), and fever (20%). The results obtained form logistic regression analysis indicated that age, place of residence, education level, health insurance status, as well as all constructs of the TPB were significant predictors for self-medication. Conclusion The findings indicated that the prevalence of self-medication among Iranian women was high. Since women have important role in shaping the family health, the issue of high prevalence among this population should be considered as a serious problem in Iran. In this regard, it is recommended to consider factors affecting self-medication among women to reduce this health threatening factors.